Comparative Analysis of Excise Tax Policy and Its Impact on Alcohol Consumption in EU Countries and Russia - Elena V. IADRENNIKOVA; Viktoriia A. KORETSKAIA-GARMASH (Communications of International Proceedings, 2020)
Government policy on excise taxes on alcohol consumption has remained a relevant research topic for scholars in Russia and abroad. Strong alcohol continues to dominate consumer preference in Russia, which leads to a number of negative consequences. This makes it ever more urgent a task to modify consumer preferences toward low alcohol beverages, wine and beer. The article analyzes government alcohol pricing policies aimed at reducing alcohol consumption in Russia and the European Union and their impact on alcohol consumption. The study compares the excise tax rates for alcohol, their patterns of change in Russia and the EU member states. Trends in the volume and structure of alcohol consumption under the influence of excise duties in Russia and the EU are examined. The author substantiates the need to improve the excise tax policy with regard to alcohol by incorporating the experience of other countries. This study seeks to analyze and assess the effectiveness of government measures to regulate the consumption of alcoholic drinks in Russia and the EU and to work out suggestions for improving the Russian system of excise taxation.
Keywords: Excise tax; alcoholic beverages; government excise tax policy on alcohol; tax rates; structure of alcohol consumption.